Corporate Panopticons: Eggers’ Exploration of Privacy and Personhood in the Age of Surveillance Capitalism - A K, Ajeesh (Surveillance & Society, 2026)
Dave Eggers’s novels The Circle (2013) and The Every (2021) explore the unsettling consequences of life under unrelenting digital scrutiny, shedding light on how constant connectivity can erode personal autonomy and reshape identity. In The Circle, Mae Holland’s rise from a private individual to a public figure demonstrates how technologies that promise social and professional benefits can, in practice, commodify human experiences. In The Every, Delaney Wells’s attempts to sabotage the company that succeeds the Circle reveal the overwhelming power of data-driven platforms and the difficulty of breaking free from them. Building on Shoshana Zuboff’s (2019a) concept of surveillance capitalism, this study examines how Eggers critiques a world where behaviour is traced, analysed, and exploited for profit. As characters navigate environments that demand perpetual sharing and content creation, they become cogs in an ecosystem that rewards performative participation over authentic connection. Sherry Turkle’s (1995, 2012, 2015) work on digital intimacy further illuminates the emotional toll of virtual interactions, illustrating how Eggers’s characters struggle to maintain genuine relationships when validation depends on algorithmic metrics. Eggers’s narratives raise urgent questions about privacy, selfhood, and agency. The relentless pursuit of transparency and “perfect” data reduces individuals to mere sources of information, leaving them vulnerable to burnout, social alienation, and a hollow sense of belonging. By focusing on Mae’s and Delaney’s personal journeys, the novels expose the hidden costs of algorithmic governance and corporate surveillance, ultimately warning readers about how unchecked data practices can undermine trust, fragment relationships, and reshape what it means to be human in a digitally dominated world.